Imaging Strategies and Outcomes in Children Hospitalized with Cervical Lymphadenitis. Issue 4 (20th November 2019) - Desai, Sanyukta; Shah, Samir S; Hall, Matt; Richardson, Troy E; Thomson, Joanna E; Network., for the Pediatric Research in Inpatient Settings (PRIS)
Abstract : OBJECTIVES: This study aimed to describe variation in imaging practices and examine the association between early imaging and outcomes in children hospitalized with cervical lymphadenitis. METHODS: This multicenter cross‐sectional study included children between two months and 18 years hospitalized with cervical lymphadenitis between 2013 and 2017. Children with complex chronic conditions, transferred from another institution, and with prior hospitalizations for lymphadenitis were excluded. To examine hospital‐level variation, we calculated the proportion of children at each hospital who received any imaging study, early imaging (conducted on day 0 of hospitalization), multiple imaging studies, and CT imaging. Generalized linear or logistic mixed effects models examined the association between early imaging and outcomes (ie, multiple imaging studies, surgical drainage, 30‐day readmission, and length of stay) while accounting for patient demographics, markers of illness duration and severity, and clustering by hospital. RESULTS: Among 10, 014 children with cervical lymphadenitis, 61% received early imaging. There was hospital‐level variation in imaging practices. Compared with children who did not receive early imaging, children who received early imaging presented increased odds of having multiple imaging studies (adjusted odds ratio [aOR] 3.0; 95% CI: 2.6‐3.6), surgical drainage (aOR 1.3, 95% CI: 1.1‐1.4), and 30‐day readmission for lymphadenitis (aOR 1.5, 95% CI: 1.2‐1.9), as well as longer lengths of stay (adjusted rate ratio 1.2, 95% CI: 1.1‐1.2). CONCLUSIONS: Children receiving early imaging had more resource utilization and intervention than those without early imaging. Our findings may represent a cascade effect, in which routinely conducted early imaging prompts clinicians to pursue additional testing and interventions in this population.